APPLICATION OF RADEC LEARNING MODEL TO IMPROVE ELEMENTARY STUDENTS' SCIENCE LITERACY ON HUMAN DIGESTIVE SYSTEM MATERIAL - Yunita Syahrani; Atep Sujana; Isrokatun Isrokatun (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2024)
This study aims to determine how science literacy before and after using the RADEC learning model, how the difference in the improvement of science literacy in the class used, namely the experimental class (RADEC model) and the control class (conventional model) and know how the implementation of science learning using the RADEC model on Human Digestive System material. The method used is Quasi Experiment with a Nonequivalent Control Group Design research design. The population of this study was a school in North Sumedang District with a research sample of grade V students totaling 112 students consisting of 56 female students and 56 male students. The instruments used were test instruments and observation sheets. The research data were processed using Microsoft Excel and SPSS applications. The data analysis technique used to process data is the average measurement using Microsoft Excel while the normality test, homogeneity test, 2-group hypothesis test (t-test and U-test), and N-gain test using SPSS. The observation sheet instrument was processed by describing the research results based on objective conditions. Literacy before using the RADEC model obtained an average of 55.9 with the low category while afterward obtained an average of 80.4 with the high category. In addition, there is a difference in the improvement of science literacy between the experimental and control classes. The experimental class test scores had a greater increase than the control class. The experimental class had an average value of 0.55 while the control class with a value of 0.30 based on the N-Gain Test. RADEC learning steps are well implemented according to its stages starting from the (Read) stage the teacher asks students to read the material, (answer) students answer pre-learning questions, (discuss) students discuss in groups, (explain) students present the results, (create) students make simple works according to creativity.